Successful Liberation from Acute Kidney Replacement Therapy in Critically Ill Patients: A Prospective Cohort Study - Suarez, Maria Irma Rodriguez [UNESP]; Ohara, Cristine Naomi [UNESP]; Kitawara, Koody Andre Hassemi [UNESP]; Zamoner, Welder [UNESP]; Balbi, Andre Luis [UNESP]; Ponce, Daniela [UNESP] (Karger Publishers, 2024)
Introduction: Recovery of kidney function to liberate patients from acute kidney replacement therapy (AKRT) is recognized as a vital patient-centered outcome. The lack of specific guidelines providing specific recommendations on therapy interruption is an important obstacle. We aimed to determine the prevalence of successful discontinuation of AKRT and its predictive factors after the elaboration of clinical protocol with these recommendations. Methodology: A prospective cohort study was performed with 156 patients at a public Brazilian university hospital between July 2020 and July 2021. Results: Success and hospital discharge were achieved for most patients (84.6% and 89%, respectively). Multivariable logistic regression analysis showed that C-reactive protein (CRP), urine output, and creatinine clearance at the time of interruption were variables associated with discontinuation success (OR: 0.943, CI: 0.905–0.983, p = 0.006; OR: 1.078, CI: 1.008–1.173, p = 0.009 and OR: 1.091, CI: 1.012–1.213, p = 0.004; respectively). The areas under the curve for CRP, urine output, and creatinine clearance at the time of interruption were 0.78, 0.62, and 0.82, respectively. Both CRP and creatinine clearance were good predictors of successful liberation of AKRT. The optimal cutoff value of them had sensitivity and specificity of 0.88 and 0.87, 0.91 and 0.90, respectively. The use of noradrenalin at the time of interruption (OR: 0.143, CI: 0.047–0.441, p = 0.001) and successful discontinuation (OR: 3.745, CI: 1.047–13.393, p = 0.042) were identified as variables associated with hospital discharge. Conclusion: Our results show the factors related to success in discontinuing AKRT are the CRP, creatinine clearances, and urinary output at the time of AKRT interruption and it was associated with lower mortality.
Keywords: Acute kidney injury; Discontinuation; Predictive factors; Renal replacement therapy; Success